Transforming somatic mutations of mammalian target of rapamycin kinase in human cancer. Issue 12 (30th October 2015) - Yamaguchi, Hiroyuki; Kawazu, Masahito; Yasuda, Takahiko; Soda, Manabu; Ueno, Toshihide; Kojima, Shinya; Yashiro, Masakazu; Yoshino, Ichiro; Ishikawa, Yuichi; Sai, Eirin; Mano, Hiroyuki
Abstract : Mammalian target of rapamycin (mTOR) is a serine–threonine kinase that acts downstream of the phosphatidylinositol 3‐kinase signaling pathway and regulates a wide range of cellular functions including transcription, translation, proliferation, apoptosis, and autophagy. Whereas genetic alterations that result in mTOR activation are frequently present in human cancers, whether the mTOR gene itself becomes an oncogene through somatic mutation has remained unclear. We have now identified a somatic non‐synonymous mutation of mTOR that results in a leucine‐to‐valine substitution at amino acid position 2209 in a specimen of large cell neuroendocrine carcinoma. The mTOR(L2209V) mutant manifested marked transforming potential in a focus formation assay with mouse 3T3 fibroblasts, and it induced the phosphorylation of p70 S6 kinase, S6 ribosomal protein, and eukaryotic translation initiation factor 4E–binding protein 1 in these cells. Examination of additional tumor specimens as well as public and in‐house databases of cancer genome mutations identified another 28 independent non‐synonymous mutations of mTOR in various cancer types, with 12 of these mutations also showing transforming ability. Most of these oncogenic mutations cluster at the interface between the kinase domain and the FAT (FRAP, ATM, TRRAP) domain in the 3‐D structure of mTOR. Transforming mTOR mutants were also found to promote 3T3 cell survival, and their oncogenic activity was sensitive to rapamycin. Our data thus show that mTOR acquires transforming activity through genetic changes in cancer, and they suggest that such tumors may be candidates for molecularly targeted therapy with mTOR inhibitors. Abstract : Activating mutations of mTOR are shown in red on the schematic protein structure.